Pengaruh Thin Capitalization, dan Transfer Pricing Terhadap Penghindaran Pajak Dimoderasi Financial Constraints - Sri Mulyani; Imar Halimah (CV. Rayyan Dwi Bharata, 2025)
The purpose of this research is to empirically test and obtain evidence regarding the influence of Thin Capitalization and Transfer Pricing on Tax Avoidance, moderated by Financial Constraints. This study uses a sample of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 The sampling technique employed is purposive sampling, where from 130 non-cyclical consumer sector companies, a sample of 25 companies was obtained over 5 years, resulting in a total of 125 data samples. The analysis used is panel data regression analysis employing a fixed effect regression model for equations I and II. The data was processed using Eviews12 software. The results indicate that both thin capitalization and transfer pricing simultaneously influence tax avoidance. The findings also show that, partially, thin capitalization affects tax avoidance, and transfer pricing affects tax avoidance. Additionally, the results indicate that financial constraints do not moderate the influence of thin capitalization, while financial constraints do moderate the influence of transfer pricing on tax avoidance.